Arsenic in Rice. Issue 1 (January 2015) - Hojsak, Iva; Braegger, Christian; Bronsky, Jiri; Campoy, Cristina; Colomb, Virginie; Decsi, Tamas; Domellöf, Magnus; Fewtrell, Mary; Mis, Nataša Fidler; Mihatsch, Walter; Molgaard, Christian; van Goudoever, Johannes
<x xml:space="preserve">Abstract</x> ABSTRACT Inorganic arsenic intake is likely to affect long-term health. High concentrations are found in some rice-based foods and drinks widely used in infants and young children. In order to reduce exposure, we recommend avoidance of rice drinks for infants and young children. For all of the rice products, strict regulation should be enforced regarding arsenic content. Moreover, infants and young children should consume a balanced diet including a variety of grains as carbohydrate sources. Although rice protein–based infant formulas are an option for infants with cows' milk protein allergy, the inorganic arsenic content should be declared and the potential risks should be considered when using these products.